2016
DOI: 10.7717/peerj.2075
|View full text |Cite
|
Sign up to set email alerts
|

Postcranial anatomy ofPissarrachampsa sera(Crocodyliformes, Baurusuchidae) from the Late Cretaceous of Brazil: insights on lifestyle and phylogenetic significance

Abstract: The postcranial anatomy of Crocodyliformes has historically been neglected, as most descriptions are based solely on skulls. Yet, the significance of the postcranium in crocodyliforms evolution is reflected in the great lifestyle diversity exhibited by the group, with members ranging from terrestrial animals to semi-aquatic and fully marine forms. Recently, studies have emphasized the importance of the postcranium. Following this trend, here we present a detailed description of the postcranial elements of Piss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 117 publications
3
84
0
Order By: Relevance
“…Based on our examination of teleosaurid skeletons and undertaking least-squares linear regression analyses of cranial and femoral lengths against total body length, we demonstrate that Teleosauridae evolved a unique body-plan which had proportionally large crania and short femora. We further demonstrate that using the cranial-tototal body length equations of three extant species, Alligator mississippiensis (Daudin, 1802), Crocodylus porosus Schneider, 1801, and Gavialis gangeticus (Gmelin, 1789) results in significant size overestimates. Additionally, we found that previous body length estimates of teleosaurids are erroneous, as they have overestimated their potential size.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Based on our examination of teleosaurid skeletons and undertaking least-squares linear regression analyses of cranial and femoral lengths against total body length, we demonstrate that Teleosauridae evolved a unique body-plan which had proportionally large crania and short femora. We further demonstrate that using the cranial-tototal body length equations of three extant species, Alligator mississippiensis (Daudin, 1802), Crocodylus porosus Schneider, 1801, and Gavialis gangeticus (Gmelin, 1789) results in significant size overestimates. Additionally, we found that previous body length estimates of teleosaurids are erroneous, as they have overestimated their potential size.…”
Section: Introductionmentioning
confidence: 71%
“…forms that evolved scaling ratios distinct from extant crocodylians (Farlow et al, 2005;Young et al, 2011;Pol et al, 2012;Godoy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…; Riff & Kellner ; Godoy et al . , ). Despite the long history of research on baurusuchids (Price ; Gasparini ), few studies have examined aspects of their ontogeny, as juvenile specimens have been rarely reported and their preserved fossils are mostly fragmentary (e.g.…”
Section: Institutional Abbreviationmentioning
confidence: 99%
“…Equations based on modern species, using either cranial (e.g., Webb & Messel, 1978;Hall & Portier, 1994;Sereno et al, 2001, Hurlburt et al, 2003Platt et al, 2009; or postcranial measurements (e.g., Bustard & Singh, 1977;Farlow et al, 2005), have predominantly been used for estimating total body size of extinct crocodylomorph species. Although some of these approaches have been claimed to work well when applied to extinct taxa (e.g., Farlow et al, 2005), they are expected to be less accurate for extinct species that have different body proportions to those of extant species (e.g., Pol et al, 2012;Young et al, 2011;2016;Godoy et al, 2016; but see Figure S1). An alternative approach that has been suggested is to use cladespecific equations that are derived from regressions using fossil specimens with complete skeletons preserved, such as the recently proposed equations for estimating body length in the highly specialised marine clade Thalattosuchia (Young et al, 2011;2016).…”
Section: Proxy For Total Body Lengthmentioning
confidence: 99%
“…For instance, their equations, using both femur and humerus circumference, have been applied to estimate body mass of fossil dinosaurs (e.g., Benson et al 2014;Carballido et al, 2017). However, due to a historical neglect of crocodylomorph postcranial anatomy, especially for Mesozoic taxa (Godoy et al, 2016), relatively less information is available on this part of the skeleton. Based on data collected for the present study, total or partial skull lengths (i.e., complete skulls or lacking only the snouts) can be measured in fossil specimens of approximately 50% of crocodylomorph species, whereas femoral and humeral shaft circumferences or lengths can only be measured in 35% of species.…”
Section: Proxy For Total Body Lengthmentioning
confidence: 99%